2023
DOI: 10.3389/fimmu.2022.1000951
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of shift work on skin autoimmune diseases

Abstract: Shift work is associated with systemic chronic inflammation, impaired host and tumor defense and dysregulated immune responses to harmless antigens such as allergens or auto-antigens. Thus, shift workers are at higher risk to develop a systemic autoimmune disease and circadian disruption with sleep impairment seem to be the key underlying mechanisms. Presumably, disturbances of the sleep-wake cycle also drive skin-specific autoimmune diseases, but epidemiological and experimental evidence so far is scarce. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 457 publications
0
4
0
Order By: Relevance
“…111 Changes in barrier properties associated with immune cell trafficking are induced by brain and blood cytokines, and even breeches to the gut barrier affect choroid plexus permeability at the endothelium. 112 While immune responses have a wellstudied circadian component, [113][114][115] direct relationships between circadian rhythms, the blood-CSF barrier, and immune cell trafficking remain to be investigated.…”
Section: Compendium: Circadian Mechanisms In Cardio/ Cerebrovascular ...mentioning
confidence: 99%
“…111 Changes in barrier properties associated with immune cell trafficking are induced by brain and blood cytokines, and even breeches to the gut barrier affect choroid plexus permeability at the endothelium. 112 While immune responses have a wellstudied circadian component, [113][114][115] direct relationships between circadian rhythms, the blood-CSF barrier, and immune cell trafficking remain to be investigated.…”
Section: Compendium: Circadian Mechanisms In Cardio/ Cerebrovascular ...mentioning
confidence: 99%
“…For example, shift work disrupts the circadian system (which virtually controls all bodily functions), often leading to chronic stress and poor sleep. These in turn trigger the onset of chronic systemic inflammation and autoimmune, infectious, oncological, and allergic skin diseases via impaired innate and acquired immunity [36].…”
Section: Skin As Stress-triggered Neuroimmunoendocrine Organmentioning
confidence: 99%
“…In vitro studies have shown that dexamethasone (Dex) can reset peripheral circadian rhythms [24]. Interestingly, the local circadian rhythm of skin cells also affects wound healing and the hair cycle [25,26], and the dysregulation of peripheral circadian rhythms has been implicated in various skin disorders [27]. Nevertheless, the underlying photoreceptive mechanisms have not been clarified.…”
Section: Introductionmentioning
confidence: 99%